The Influence of Leadership Quality on Teachers' Performance through Soft Skills and Teaching Creativity - Hastuti Mulang; Ismail HA (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine and analyze the effect of Leadership Quality on Teacher Performance through Soft Competence and Teacher Teaching Creativity at MAN 2 bulukumba. This type of research uses a quantitative approach. Sampling using total sampling, with a sample of 82 teachers. The data sources used in the study are primary data and secondary data. Primary data were obtained from the distribution of questionnaires, while secondary data were obtained from journals, books, and previous studies. Primary data was obtained from the distribution of questionnaires consisting of 22 questions. The measuring scale used is the Likert Scale. Data analysis and processing in this study used multiple linear regression analysis and path analysis using the SPSS ver.26 for Windows program. The results concluded that leadership quality can improve teacher performance directly and indirectly through soft competence and teaching creativity. 1) Leadership quality has a positive and significant effect on teachers' soft competence; 2) Leadership quality has a positive and significant effect on teachers' teaching creativity; 3) Soft competence has a positive and significant effect on teachers' teaching creativity; 4) Leadership quality has a positive and significant effect on teacher performance; 5) Soft competence has a positive and significant effect on teacher performance; 6) Teaching creativity has a positive and significant effect on teacher performance; 7) Leadership quality has a positive and significant effect on teacher performance through soft competence; 8) Leadership quality has a positive and significant effect on teacher performance through teaching creativity.